2003
DOI: 10.1111/j.1572-0241.2003.07384.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonpathogenic bacteria on cytokine secretion by human intestinal mucosa

Abstract: Nonpathogenic bacteria interact with human intestinal mucosa and can induce changes in cytokine production that are strain specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(26 citation statements)
references
References 19 publications
3
22
0
1
Order By: Relevance
“…However, in line with our results, experiments with human intestinal mucosal explants have shown that TNF, IL-8, and IL-10 are produced in response to E. coli but not in response to Lactobacillus casei (11). Furthermore, the gut mucosal DCs predominantly consist of myeloid DCs, which presumably are of monocyte origin (7).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, in line with our results, experiments with human intestinal mucosal explants have shown that TNF, IL-8, and IL-10 are produced in response to E. coli but not in response to Lactobacillus casei (11). Furthermore, the gut mucosal DCs predominantly consist of myeloid DCs, which presumably are of monocyte origin (7).…”
Section: Discussionsupporting
confidence: 89%
“…lectins (11). Nevertheless, microbes are likely to be recognized by a complex combination of receptors, which by acting together decide the outcome of the response.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased levels of Bifi dobacterium and Lactobacillus strains have been described in fecal samples, whereas raised counts of Enterococcus and Bacteroides species are found in infl amed mucosa of patients with IBD. High levels of infl ammatory cytokines (TNF-α and IL-1β) and IL-8 are produced by infl amed colonic mucosa of both UC and CD patients, [65][66][67][68][69] while the role of autoantibodies remains to be determined. 70 In addition, lamina propria T cells from IBD patients secrete elevated levels of IL-6, and IL-6/STAT-3 signaling is upregulated.…”
Section: Probiotics In Infl Ammatory Diseases Of the Bowelmentioning
confidence: 99%
“…[67][68][69] Downregulation of IL-6, which can exhibit antiapoptotic activity, may play a role in this process. 69 Indeed, in a mouse model of chronic colitis, treatment with neutralizing IL-6 receptor antibodies prevented macroscopic signs of infl ammation in the colon while markedly increasing the number of lamina propria CD4+ T cells undergoing apoptosis.…”
Section: Probiotics In Infl Ammatory Diseases Of the Bowelmentioning
confidence: 99%
“…A strain of Lactobacillus casei, DN-114 001, has been shown to decrease the secretion of TNF-␣ from the inflammed ileum of Crohn's disease patients (8,9). The beneficial effect of probiotics is proposed to be due, at least in part, to interference with the innate immune system and possibly the orientation of adaptive immunity.…”
mentioning
confidence: 99%